2019
DOI: 10.1111/jfbc.12818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat, ultrasound, and microwave processing on the stability and antioxidant activity of delphinidin and petunidin

Abstract: The effects of conventional heating, ultrasonic, and microwave treatments on the stability and antioxidant activities of anthocyanidin standards (delphinidin and petunidin) were studied. The antioxidant activities of delphinidin and petunidin significantly decreased during the treatments, which suggested that the antioxidant activities of the degradation products were lower than that of anthocyanidin. In addition, the degradation of delphinidin and petunidin followed first‐order reaction kinetics. The kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Furthermore, after incubation at 45 • C for 24 h, there was little to no pigment remaining in these samples; this negates the possibility of PACN formation with increased incubation times. Delphinidin's and petunidin's propensity to degrade during prolonged heating [42,43] may explain the absence or reduced formation of PACNs in these samples. The significantly higher yields of malvidin-and cyanidin-derived PACNs may explain why most reports have especially identified these derivatives [11,14,16,19,25,44,45].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, after incubation at 45 • C for 24 h, there was little to no pigment remaining in these samples; this negates the possibility of PACN formation with increased incubation times. Delphinidin's and petunidin's propensity to degrade during prolonged heating [42,43] may explain the absence or reduced formation of PACNs in these samples. The significantly higher yields of malvidin-and cyanidin-derived PACNs may explain why most reports have especially identified these derivatives [11,14,16,19,25,44,45].…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that the presence of a glucose residue at position 5 (ring A) has a minimal influence on the kinetics of the proton transfer equilibrium, but significantly increases the hydration rate, slowing down the reverse reaction [13]. Similarly, other authors suggested that the thermal degradation of anthocyanins, in particular at pH 3.5, follows the pathway of intermediate chalcone and final derivatives of aldehyde and benzoic acid, structurally differentiated based on the corresponding anthocyanidin [15][16][17][18][19], as illustrated in Figure 2 for the most abundantly distributed anthocyanidins in fruits and vegetables (cyanidin, pelargonidin, delphinidin, malvidin and petunidin). Combined hydrolytic and autooxidative reactions are probably involved [20].…”
Section: Kinetics and Thermal Degradation Route Of Anthocyaninsmentioning
confidence: 99%
“…Similar behavior was reported by Liazid et al [ 144 ] in grape skin anthocyanins, in which MW treatment remarkably enhanced the acylated glucoside anthocyanin recovery regarding monoglucoside anthocyanins compared to the solid-liquid maceration classical method. Wang et al [ 145 ] observed that delphinidin was more stable than petunidin under MW treatment. Meanwhile, Sivamaruthi et al [ 146 ] verified that petunidin was more stable than cyanidin after MW exposure.…”
Section: Innovative Processes For Anthocyanin Extraction From Agri-food By-productsmentioning
confidence: 99%